49th IEEE Conference on Decision and Control (CDC) 2010
DOI: 10.1109/cdc.2010.5718094
|View full text |Cite
|
Sign up to set email alerts
|

Robust controller design by convex optimization based on finite frequency samples of spectral models

Abstract: Abstract-Some frequency-domain controller design problems are solved using a finite number of frequency samples. Consequently, the performance and stability conditions are not guaranteed for the frequencies between the frequency samples. In this paper, all possible interpolants between the frequency samples of the open-loop system are bounded using convex constraints on a linearly parameterized controller. These constraints are integrated in a method which solves an H∞ control problem based on spectral models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…that is equivalent to (6). Moreover, it can be shown that the number of encirclements of the critical point by L and L d is equal.…”
Section: Design Specificationsmentioning
confidence: 92%
See 1 more Smart Citation
“…that is equivalent to (6). Moreover, it can be shown that the number of encirclements of the critical point by L and L d is equal.…”
Section: Design Specificationsmentioning
confidence: 92%
“…In this case a scenario approach can be used that guarantees the satisfaction of all constraints with a probability level when they are only satisfied for a finite number of randomly chosen scheduling parameters [3]. Some of the effects of gridding in frequency and additional constraints that can be imposed for ensuring good behavior between the grid points are described in [6].…”
Section: Optimization Problemmentioning
confidence: 99%
“…This can be done because a second order system can be considered as the sum of two first order systems with a pair of complex conjugated poles (10). The final analysis was done on one of these first order systemsG (s) = b s−p in (13), the other one was neglected because it did not significantly contribute to the error.…”
Section: Normalised First Order Systemmentioning
confidence: 99%
“…Although this paper focusses on the LPM, the reader should be aware that the results can also be applied to other problems where a polynomial approximation of the frequency response function is needed, like for example control design [10], [11], [12]. In some design techniques, a controller is designed directly from a discrete set of frequency response function measurements that need to be interpolated.…”
Section: Introductionmentioning
confidence: 99%
“…All the values in Table 3 are in per-unit system. ω is the desired closed-loop bandwidth [17] [22]. Typically, the bandwidth is the range of frequencies for which the gain is significant.…”
Section: Choice Of Operating Pointsmentioning
confidence: 99%